Diversity of DHA-1-encoding plasmids in Klebsiella pneumoniae isolates from 16 French hospitals. (27th July 2018) - Hennequin, Claire; Chlilek, Alexandre; Beyrouthy, Racha; Bonnet, Richard; Robin, Frédéric
Abstract: Objectives: To provide new insights into the spread of plasmidic cephalosporinase DHA-1, 16 strains of Klebsiella pneumoniae and a strain of Klebsiella variicola producing DHA-1 were isolated between January 2012 and December 2013 in six regions of France and two French overseas departments and territories. Methods: Disc diffusion assays, isoelectric focusing and PCRs were used to characterize the plasmidic DHA-1 β-lactamase. Plasmid analysis was performed by the method of Kado and Liu and WGS. Virulence of the strains was studied by biofilm formation and the survival of Drosophila . Results: The strains were of low virulence and had one to three plasmids including one of various sizes ( ∼ 40 to 319 kb) mediating DHA-1. Nine strains belonged to ST11 and possessed a pKPS30-type DHA-1 plasmid of the IncR (incompatibility) group. A strain of ST307 possessed pENVA, a DHA-1 plasmid of the IncH-type group. The seven remaining plasmids were unknown. Three belonged to the IncL/M group. They were closely related and their sequences were determined. One of the four remaining strains was chosen for further investigation. This strain of ST16 had two plasmids, a pUUH239.2-related plasmid and a new DHA-1 plasmid of ∼ 319 kb of IncHI2 type. Conclusions: These findings demonstrate the major role of the pKPS30-type plasmid in the spread of DHA-1 cephalosporinase in France and provide evidence of two new emerging plasmids carrying this enzyme.